2007
DOI: 10.5194/bg-4-11-2007
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen assimilation and short term retention in a nutrient-rich tidal freshwater marsh – a whole ecosystem <sup>15</sup>N enrichment study

Abstract: Abstract. An intact tidal freshwater marsh system (3477 m 2 ) was labelled by adding 15 N-ammonium as a tracer to the flood water inundating the ecosystem. The appearance and retention of 15 N-label in different marsh components (leaves, roots, sediment, leaf litter and invertebrate fauna) was followed over 15 days. This allowed us to elucidate the direct assimilation and dependence on creek-water nitrogen on a relatively short term and provided an unbiased assessment of the relative importance of the various … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 41 publications
1
24
0
Order By: Relevance
“…Isotopically labeled nutrients have been used to measure nutrient uptake for individual organisms within a community (Cornelisen & Thomas 2006, Morris et al 2008, to determine the relationship between seagrass and epiphyte nutrient uptake (McRoy & Goering 1974, Lepoint et al 2007, and to trace distribution of nutrients among community components (Koop et al 2001, Cornelisen & Thomas 2006, Gribsholt et al 2006). …”
Section: Methodsmentioning
confidence: 99%
“…Isotopically labeled nutrients have been used to measure nutrient uptake for individual organisms within a community (Cornelisen & Thomas 2006, Morris et al 2008, to determine the relationship between seagrass and epiphyte nutrient uptake (McRoy & Goering 1974, Lepoint et al 2007, and to trace distribution of nutrients among community components (Koop et al 2001, Cornelisen & Thomas 2006, Gribsholt et al 2006). …”
Section: Methodsmentioning
confidence: 99%
“…Coupled nitrification-denitrification drives gaseous losses of N from salt marsh soils (Tobias et al 2001, Dollhopf et al 2005, Hamersley and Howes 2005, but microbially mediated processes can also contribute to long-term N retention (Gribsholt et al 2007, Gribsholt et al 2009). Denitrification can be a major N loss pathway in salt marshes (Kaplan et al 1979) accounting for up to 77% of ecosystem N losses (White and Howes 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Both studies of North American systems revealed that exchanges of dissolved inorganic nitrogen (DIN; ammonium and nitrate) between the marsh and tidal water are relatively small compared to internal marsh nitrogen recycling. Using deliberate 15 N tracer additions to intact ecosystems, Gribsholt et al (2005Gribsholt et al ( , 2006Gribsholt et al ( , 2007 studied the fate of watershed-derived ammonium in a tidal freshwater marsh fringing the Scheldt estuary (Belgium). These marsh-scale experiments conducted during the early and late growing seasons confirmed the limited exchange between marshes and tidal waters because the majority of the ammonium entering the marsh was exported again by subsequent tides.…”
mentioning
confidence: 99%
“…These marsh-scale experiments conducted during the early and late growing seasons confirmed the limited exchange between marshes and tidal waters because the majority of the ammonium entering the marsh was exported again by subsequent tides. Moreover, they revealed that tidal freshwater marshes function primarily as nutrient transformers, because nitrification represented the largest sink of added 15 N (Gribsholt et al 2005(Gribsholt et al , 2006. About 4% of the added 15 N-NH z 4 was retained by the marsh ecosystem during the 2-week study periods.…”
mentioning
confidence: 99%
See 1 more Smart Citation